CONTROL OF ENERGY-EFFICIENCY IN PRODUCTION AND IMPLEMENTATION OF NEWEST ENERGYSAVING TECHNOLOGIES AT RUP «BMZ» - A. L. Sugojd (Литьë и металлургия, 2010)
The up-to-date energy-efficient technologies at RUP«BMZ» are given.